2012
DOI: 10.4236/ijg.2012.35107
|View full text |Cite
|
Sign up to set email alerts
|

U-Pb Geochronology of the Jebba Granitic Gneiss and Its Implications for the Paleoproterozoic Evolution of Jebba Area, Southwestern Nigeria

Abstract: Jebba area southwestern Nigeria forms part of the Nigerian basement complex which lies in the Neoproterozoic PanAfrican mobile belt. It is underlain by several lithological units among which is a polydeformed granitic gneiss. This rock has been dated by LA-ICP-MS yielding a concordant U-Pb zircon age of 2207 ± 20 Ma indicating the crystallization age of the granite protolith. This early Rhyacian age and its affinity with within-plate granites indicates emplacement during crustal extension and rifting preceding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Relative weight percentage of each of oxides of these elements is different in Granite Gneiss samples extracted from different geological locations. According to literature, after SiO 2 most abundant oxides are Al 2 O 3 , Fe 2 O 3 , and K 2 O (Odunyemi & Olufemi, 2011;Okonkwo & Ganev, 2012;Rutland & Sutherland, 1967).…”
Section: Determination Of Atomic Number Density Of Species Found In Gmentioning
confidence: 99%
“…Relative weight percentage of each of oxides of these elements is different in Granite Gneiss samples extracted from different geological locations. According to literature, after SiO 2 most abundant oxides are Al 2 O 3 , Fe 2 O 3 , and K 2 O (Odunyemi & Olufemi, 2011;Okonkwo & Ganev, 2012;Rutland & Sutherland, 1967).…”
Section: Determination Of Atomic Number Density Of Species Found In Gmentioning
confidence: 99%
“…[5][6][7][8] have shown that the Nigerian Basement Complex comprises Archean and Proterozoic rocks and bears the imprints of the Liberian (2700 ± 200 Ma), Eburnean (2000 ± 200 Ma) orogenic events. This basement was a zone of reactivation and orogenesis during the PanAfrican (600 ± 150 Ma) event [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Similar Palaeoproterozoic orthogneisses have been documented from other parts of southwestern sector of the Nigerian basement complex (Fig. 1c) e.g., Ibadan granitic gneiss (Grant, 1970), Igbeti augen gneiss (Rahaman et al, 1983), Itakpe Hill migmatitic gneiss (Caen-Vachette and Umeji, 1987), Kabba Granodioritic Gneiss (Annor 1995), Jebba Granitic Gneiss (Okonkwo and Ganev 2012). These data indicate that the Palaeoproterozoic was an important period of crustal growth in southwestern Nigeria and confirm that the Eburnean orogeny affected this sector of the Nigerian Basement complex.…”
Section: Discussionmentioning
confidence: 65%
“…They include migmatites, orthogneisses, paragneisses as well as metabasic rocks which have attained amphibolites facies metamorphic conditions and in a few places the granulite facies conditions. Geochronological data from gneisses in southwestern Nigeria include late Archean and Paleoproterozoic ages (Oversby, 1975;Pidgeon et al, 1976;Rahaman et al, 1983;Caen-Vachette and Umeji, 1987;Rahaman, 1988;Annor 1995;Okonkwo and Ganev 2012).…”
Section: Geological Settingmentioning
confidence: 99%